2007
DOI: 10.1111/j.1600-0765.2007.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Crevicular fluid endothelin‐1 levels in periodontal health and disease

Abstract: The results showed that all the gingival crevicular fluid samples were negative for the endothelin-1 molecule. Therefore, endothelin-1 cannot be considered as a potential biomarker of periodontal disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…On the following day, the site for sample collection was well isolated and supragingival plaque removed while taking care not to make contact with the marginal gingiva. A standardized volume of 3 μl GCF was collected by placing a microcapillary pipette (Sigma-Aldrich, St. Louis, MO, USA) at the entrance of the gingival sulcus (extrasulcular method) 32) . Micro-pipettes contaminated with blood or saliva were excluded from the study.…”
Section: Selection Of Site and Collection Of Gcf Fluidmentioning
confidence: 99%
“…On the following day, the site for sample collection was well isolated and supragingival plaque removed while taking care not to make contact with the marginal gingiva. A standardized volume of 3 μl GCF was collected by placing a microcapillary pipette (Sigma-Aldrich, St. Louis, MO, USA) at the entrance of the gingival sulcus (extrasulcular method) 32) . Micro-pipettes contaminated with blood or saliva were excluded from the study.…”
Section: Selection Of Site and Collection Of Gcf Fluidmentioning
confidence: 99%
“…Also, periodontal therapy improves endothelium-dependent vasodilation in normotensive and hypertensive patients [36-38]. Patients with PD present higher levels of endothelin-1 compared with those without PD [39, 40]. A nitric oxide synthase inhibitor level (asymmetric dimethylarginine) associated with endothelial dysfunction was higher in hypertensive patients with PD [41].…”
Section: Pathophysiologic Mechanisms That Could Explain the Associatimentioning
confidence: 99%
“…The expression of ET-1 was strongly associated in the gingival tissue and endothelial cells during periodontitis 14 . More specifically, a clinical study found that, in gingival crevicular fluid, the ET-1 level increased with the progression of the periodontitis, and also that ET-1 was involved in the regulation of IL-1b expression in gingival tissues 15,16 .…”
mentioning
confidence: 99%